A Review on Herbal Approach to Treat Rheumatoid Arthritis - Trivedi, Dr. Rahul (Asian Journal of Pharmaceutics (AJP), 2023)
Rheumatoid arthritis (RA) is an autoimmune disorder. The disease mainly affects more than one joint in the body. Many people are affected by this disease worldwide. RA is a long-term progressive disorder with different stages. As the disease progresses, the condition of the joints gets worse and joint function terminates at last. It also affects other organs in the body. Many factors, including environmental, age, weight, genetics, and lifestyle, are responsible for RA. Several etiological factors, such as autoantibodies, inflammatory mediators, and genes, are responsible for the generation of RA. The symptoms of the disease include swelling, pain, loss of appetite, joint inflammation, fatigue, and pericarditis. The treatment objective for RA includes reducing pain and inflammation and preventing joint dysfunction as well as joint deformity. Various drugs, such as non-steroidal anti-inflammatory drugs, steroids, and disease-modifying anti-rheumatic drugs, are used to alleviate the symptoms of RA. The uses of synthetic drugs are associated with several life-threatening side effects. These side effects of synthetic drugs are the main thirst of peoples for searching alternative medicines in RA. The main objective of this study is to highlight the use of herbal medicines for RA for patient benefits. Herbal medicines and isolated phytoconstituents from herbal drugs have the advantages of low cost, easy availability, better patient acceptance, and very few side effects. These drugs also improve the patient’s condition and reduce stress. Many researchers have proven the efficacy of herbal drugs and phytoconstituents for RA patients. In this study, we are aiming to draw attention to the need to increase the use of herbal drugs for the treatment of RA.